Like streams to the ocean : notes on ego, love, and the things that make us who we are - Jenkins, Jedidiah (Convergent, 2021)
"A moving meditation on the hidden, sometimes difficult topics we must consider to live an authentic life, from the New York Times bestselling author of To Shake the Sleeping Self. We aren't born into a self. It is created without our consent, built on top of our circumstances, the off-handed comments we hear from others, and the moments that scared us most when we were young. But in the busyness of our daily life, we rarely get the chance to think clearly about the questions that matter most. Who am I? Where do I belong? How much of who I am and what I do boils down to avoiding the things that make me feel small? We tuck these questions into the corner of our minds, but they drive our behavior far more than we give them credit for, even after we become adults. Writing with the passion and clarity that made his debut, To Shake the Sleeping Self, a national bestseller, Jenkins makes space to explore the seven topics we must think about in order to live a deeply considered life: ego, family, work, love, nature, death, and the soul. He considers the experiences that shape us into who we are, whether they're as heart-pounding as a rafting trip through the whitewater of the Grand Canyon, or as ordinary as the moment when we look in the mirror each morning. Through it all, Jenkins leads readers on a wide-ranging conversation about finding fulfillment in the people and places around us, and discovering the courage to show our deepest selves to the world. Like Streams to the Ocean is a profound reflection from one of our most original writers, a necessary read for anyone seeking a companion on the road to understanding"--